Unique observations of a geomagnetic SI+ − SI− pair: Solar sources and associated solar wind fluctuations - Rastogi, R.G.; Janardhan, P.; Ahmed, K.; Das, A.C.; Bisoi, Susanta K. (My University, 2010)
This paper describes the occurrence of a pair of oppositely directed sudden impulses (SI) in the geomagnetic field (ΔX) at ground stations, called SI+ − SI− pairs, that occurred between 1835 UT and 2300 UT on 23 April 1998. The SI+ − SI− pair was closely correlated with corresponding variations in the solar wind density, while solar wind velocity and the southward component of the interplanetary magnetic field (Bz) did not show any correspondence. Further, this event had no source on the visible solar disk. However, a rear-side partial halo coronal mass ejection (CME) and an M1.4 class solar flare behind the west limb took place on 20 April 1998, the date corresponding to the traceback location of the solar wind flows. This event presents empirical evidence, which to our knowledge is the most convincing evidence for the association of specific solar events to the observations of an SI+ − SI− pair. In addition, it shows that it is possible for a rear-side solar flare to propagate a shock toward the Earth.
Keywords: Solar wind fluctuations; Geomagnetic; Sudden impulses; Coronal mass ejection; Interplanetary magnetic field; Solar wind